2008
DOI: 10.1002/asna.200811050
|View full text |Cite
|
Sign up to set email alerts
|

The turbulent ISM and the stellar IMF

Abstract: In this contribution, we focus on the role that turbulence can play in setting the initial mass function (IMF) of stars. Two theories are contrasted. In the first, the so-called 'turbulent' fragmentation theory, the turbulence is directly responsible for breaking up the cloud into 'cores' which go on to form either a single star or a small N system. In such a picture, the IMF is primordial, since the mass reservoir form the young protostellar system is assumed to be set by the mass of the natal core. In the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This ratio may vary from 0.5 up to 10 with the mean being approximately 1 (Solomon et al 1987;Rosolowsky 2007;Hernandez & Tan 2015). Simulations have shown that dense, self-gravitating clumps can still fragment out of clouds that are globally unbound (Clark et al 2005;Clark & Klessen 2008;Bonnell et al 2011). Furthermore, the star formation efficiency is naturally lowered in unbound clouds (Padoan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This ratio may vary from 0.5 up to 10 with the mean being approximately 1 (Solomon et al 1987;Rosolowsky 2007;Hernandez & Tan 2015). Simulations have shown that dense, self-gravitating clumps can still fragment out of clouds that are globally unbound (Clark et al 2005;Clark & Klessen 2008;Bonnell et al 2011). Furthermore, the star formation efficiency is naturally lowered in unbound clouds (Padoan et al 2012).…”
Section: Introductionmentioning
confidence: 99%